Identifying the Extra-Curricular Research Needs of the Students of Medical Sciences - Babaei Heydarabadi, Akbar; Araban, Marzieh; Mohamadian, Hashem; Hatami, Esmaeil; Rezaeian, Elahe; Bavi, Saad (International Journal of Education and Cognitive Sciences, 2022)
Introduction: Research is one of the tools for improving the ability of students, regular and controlled activity, which studies phenomena to explore and expand knowledge. Extra-curricular activities are one of the ways to increase students' knowledge in this field. Since the first step in the implementation of any educational program is the identification of priorities, the present study aimed to identify the needs of students in the Jundishapur University of Medical Sciences in Ahwaz.Methods: This study was conducted using qualitative approach and conventional content analysis method. The population includes students from Jundishapur University of Ahvaz that were selected based on purpose. The data was collected through semi-structured interviews conducted by two trained scholars using voice recorder and simultaneous interview writing. Then the data was coded and analyzed. Results: In the present study, a total of 27 students with an average age of 22.93 with a standard deviation of 2.147 and a sexual distribution of 48.1% were males and 51.9% females. Of the interviews with the students, 55 workshops were finally identified. They were categorized into two main categories dependent on the software and independent of the software. Which belonged to the software-dependent, two-class “software dependent to the Internet” and “independent of the Internet”. The software independent class is classified into 5 sub class.Conclusion: This study shows the needs of medical students in research field. It is recommended that the research research assistance and the research committee consider these needs in order to formulate research plans.